Modified Entropy Scaling of the Transport Properties of the Lennard-Jones Fluid - Bell, Ian H. (J Phys Chem B, 2019)
Rosenfeld proposed two different scaling approaches to model the transport properties of fluids, separated by twenty-two years, one valid in the dilute gas, and another in the liquid phase. In this work, we demonstrate that these two limiting cases can be connected through the use of a novel approach to scaling transport properties and an empirical bridging function. This approach, which is empirical and not derived from theory, is used to generate reference correlations for the transport properties of the Lennard-Jones 12–6 potentials of viscosity, thermal conductivity, and self-diffusion. This approach, with a very simple functional form, allows for the reproduction of the most accurate simulation data to within nearly their statistical uncertainty. The correlations are used to confirm that for the Lennard-Jones fluid the appropriately scaled transport properties are nearly monovariate functions of the excess entropy from low-density gases into the supercooled phase and up to extreme temperatures. This study represents the most comprehensive meta-study of the transport properties of the Lennard-Jones fluid to date.